The Origins of the (Cooperative) Species: Raiffeisen Banking in the Netherlands, 1898–1909 - Christopher L. Colvin; Stuart Henderson; John D. Turner (European Historical Economics Society (EHES), 2018)
Cooperatively-owned Raiffeisen banks first emerged in the Netherlands in the late 1890s and spread rapidly across the country. Using a new dataset, we investigate the determinants of their market entry and early performance. We find that the cooperative organisational form, when allied to a change in the structure of Dutch agriculture and the socioreligious pillarisation of Dutch society, was an important factor explaining their entry into rural financial markets. While religious organisations provided a necessary impetus for the emergence of Raiffeisen banks, the economic advantages associated with the cooperative organisational form ensured the subsequent survival and success of these banks.
Keywords: G21; N23; N83; 330; Cooperative banking; the Netherlands; Raiffeisen; religion